(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This study presents a systematic semantic-pragmatic analysis of the expression of cultural concepts through linguistic units in the Oghuz dialects of the Turkic language family. Moving beyond the traditional dialectological focus on phonetic and morphological features, the research adopts an integrative theoretical framework grounded in linguoculturology and cognitive linguistics to explore the mechanisms by which dialectal forms encode collective cultural knowledge and social experience. Methodologically, the study employs contextual analysis, semantic field analysis, and paremiological investigation, enabling a comprehensive examination of the multilayered organization of cultural meanings. The findings reveal that the expression of cultural concepts in Oghuz dialects operates across three interrelated levels: lexical nomination, phraseological representation, and paremiological codification. Hospitality is conceptualized not only as an ethical value but as a socially regulated institution closely associated with communal reputation and cohesion. The concept of honor functions as a central mechanism of social regulation, embedded in kinship structures and collective responsibility. Furthermore, the analysis demonstrates that Oghuz dialects preserve nuanced pragmatic meanings and archaic semantic patterns that tend to be neutralized or reduced in standardized literary language. Overall, the study advances a deeper theoretical understanding of dialects as dynamic carriers of cultural memory and provides a methodological basis for further research in comparative Turkic linguistics, discourse analysis, and dialect lexicography.